Інтерактивні методи навчання в професійно-педагогічній підготовці майбутніх учителів фізичної культури / тренерів - Равлюк, Тетяна (My University, 2025)
The relevance of applying interactive teaching methods is driven by contemporary challenges in education, particularly digitalization, the need to develop critical thinking, creativity, and teamwork skills. The implementation of this goal is facilitated by equipping future physical education teachers and coaches with pedagogically oriented disciplines, such as “Pedagogical Mastery in Managing the Educational Process" and "Pedagogy with Basics of Pedagogical Mastery." This article establishes a connection between the concepts of “method,” “teaching methods,” and “interactive teaching methods,” classifies traditional and interactive methods, and identifies criteria for the effectiveness of interactive teaching methods in higher education. The results of a survey among second-year students majoring in 014.11 Secondary Education (Physical Education) (Educational Program “Physical Education”) and first-year students majoring in 017 Physical Education and Sports (Educational Program “Physical Education and Sports”) at the bachelor’s level at Yuriy Fedkovych Chernivtsi National University are analyzed. Of the respondents, 82.4% of second-year students and 74.5% of first-year students reported that their expectations of the discipline and conducted classes were fully met. The students’ responses indicated positive impressions of interactive teaching methods and their significance in the professional development of future specialists. The following criteria for the effectiveness of interactive teaching methods were identified: Cognitive activity (engaging students in active knowledge acquisition through interaction, discussions, and independent activities); Motivation (stimulating interest in learning, emphasizing the practical significance of knowledge); Active informativeness (mastering structured knowledge with opportunities for its application); Activation of thinking (developing critical and analytical thinking through creative tasks); Collaboration (forming teamwork skills through group projects, discussions, and joint tasks); Effectiveness (evaluating students' achievements that reflect real learning outcomes).
Keywords: method, teaching methods, interactive teaching methods